Effect of spinal mobilization with leg movement as an adjunct to neural mobilization and conventional therapy in patients with lumbar radiculopathy: Randomized controlled trial - Subarna Das; Praveen; Raju (Journal of Medical and Scientific Research, 2018)
Background: In lumbar radiculopathy there is compression or inflammation of a spinal nerve and it may be accompanied by numbness and tingling, muscle weakness or loss of spinal reflexes in one or both lower limbs. Conventional physiotherapy which includes back extension exercises has varying degree of success in pain and functional outcome in lumbar radiculopathy. Mulligan's spinal mobilization with limb movement (SMWLM) and Shacklock's neural tissue mobilization are few of the techniques employed in the management of lumbar radiculopathy. The purpose of the study was to find out whether spinal mobilization with leg movement as an adjunct to neural mobilization and conventional therapy could bring better outcome in patients when compared to conventional therapy or neural mobilization and conventional therapy.